2021
DOI: 10.1530/ec-21-0192
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of thyroid nodule histopathology by expert ultrasound evaluation

Abstract: Objective: The basis of thyroid nodule diagnostics is ultrasound guided fine needle biopsy with cytological evaluation (FNC), if US appearance is not clearly benign. The aim of this study was to investigate the predictive potential of dedicated, expert high resolution ultrasound, to see if histopathological entities of thyroid nodules can be diagnosed without invasive FNC biopsies. Design: Prospective case cohort study. Methods: 180 patients with 221 thyroid nodules were examined with ultrasound and prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Most existing studies evaluating ACR-TIRADS in adulthood have determined that the system score is useful for managing thyroid nodules and reducing the number of unnecessary FNAB, while some concerns remain about its reliability in evaluating nodules of indeterminate cytology (37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51). Among the different TIRADS, ACR-TIRADS was ranked as the best performing classification for identifying high-risk nodules and unnecessary FNABs (35, 36, 52-60), although a missed malignancy diagnosis occurred in 10.2-20% of cases in which ACR-TIRADS have not indicated the need for FNAB (46,55,61).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most existing studies evaluating ACR-TIRADS in adulthood have determined that the system score is useful for managing thyroid nodules and reducing the number of unnecessary FNAB, while some concerns remain about its reliability in evaluating nodules of indeterminate cytology (37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51). Among the different TIRADS, ACR-TIRADS was ranked as the best performing classification for identifying high-risk nodules and unnecessary FNABs (35, 36, 52-60), although a missed malignancy diagnosis occurred in 10.2-20% of cases in which ACR-TIRADS have not indicated the need for FNAB (46,55,61).…”
Section: Discussionmentioning
confidence: 99%
“…Most existing studies evaluating ACR-TIRADS in adulthood have established that the score is useful for managing thyroid nodules and reducing the number of unnecessary FNAB procedures, while there are some concerns about its reliability for the evaluation of nodules with indeterminate cytology (37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51). Among the different TIRADS classification systems, ACR-TIRADS has been indicated as the most accurate classification system for identifying high-risk nodules and preventing most unnecessary FNABs (35, 36, 52-60), although in 10.2-96 20% of cases a failure to diagnose malignancy has been reported (46,55,61).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some of our findings suggested that DTC in the Philippines is more advanced at presentation: ultrasound showed more solid nodules, micro-calcifications, larger tumors, and multi-nodular disease than observed in Qatar, features that suggest thryoid cancer risk or development of multiple recurrences [ 8 , 41 ]; patients presented with higher tumor burden (less stage I, more stage IV disease) [ 11 , 22 ]; and TNM classification showed that 4.7% of patients in the Philippines had distant metastasis (M1) [ 11 ] vs 0% in Qatar. Collectively, the above clinical, ultrasound and histopathology findings suggested that DTC among Filipinos in Qatar appears to behave in a quite dissimilar manner compared to that in the Philippines.…”
Section: Discussionmentioning
confidence: 99%